2014
DOI: 10.1016/j.ultramic.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Imaging endosomes and autophagosomes in whole mammalian cells using correlative cryo-fluorescence and cryo-soft X-ray microscopy (cryo-CLXM)

Abstract: Cryo-soft X-ray tomography (cryo-SXT) is a powerful imaging technique that can extract ultrastructural information from whole, unstained mammalian cells as close to the living state as possible. Subcellular organelles including the nucleus, the Golgi apparatus and mitochondria have been identified by morphology alone, due to the similarity in contrast to transmission electron micrographs. In this study, we used cryo-SXT to image endosomes and autophagosomes, organelles that are particularly susceptible to chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 54 publications
4
95
0
5
Order By: Relevance
“…Electron tomography examinations of the omegasome ultrastructure have revealed that the extremities of the expanding phagophore are indeed physically connected with the ER, supporting this idea (Hayashi-Nishino et al, 2009;Ylä-Anttila et al, 2009). In addition, two more recent studies that combined correlative light and electron microscopy have shown that omegasomes arise from hotspots in the ER and connect to it through thin tubular membranes (Duke et al, 2014;Uemura et al, 2014). The association between these two organelles could be essential for the efficient supply of the enormous quantities of lipids that are required to form autophagosomes.…”
Section: Model II -Eres As a Scaffold For Autophagosome Biogenesismentioning
confidence: 99%
“…Electron tomography examinations of the omegasome ultrastructure have revealed that the extremities of the expanding phagophore are indeed physically connected with the ER, supporting this idea (Hayashi-Nishino et al, 2009;Ylä-Anttila et al, 2009). In addition, two more recent studies that combined correlative light and electron microscopy have shown that omegasomes arise from hotspots in the ER and connect to it through thin tubular membranes (Duke et al, 2014;Uemura et al, 2014). The association between these two organelles could be essential for the efficient supply of the enormous quantities of lipids that are required to form autophagosomes.…”
Section: Model II -Eres As a Scaffold For Autophagosome Biogenesismentioning
confidence: 99%
“…Most work performed on SXT microscopes addresses samples a few microns thick [4,[12][13][14][15][16][17][18]. Depending on the ratio between the sample thickness and the DOF, standard reconstruction algorithms introduce different artifacts which can be better estimated once the experimental DOF is known [19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mammalian ATG9 is not stably incorporated into the isolation membrane or autophagosomes but is instead transiently associated with the omegasome, a phosphatidylinositol 3-phosphate (PI3P)-enriched endoplasmic reticulum (ER) subdomain (5). Cryomicroscopy studies have shown a close association between ATG9 vesicles and the omegasome structure (7), together with the presence of ATG9 on tubulovesicular membranes surrounding autophagosomes (5). A recent finding by livecell imaging indicates that autophagosome formation occurs where ATG9 vesicles coalesce with the ER (8).…”
mentioning
confidence: 99%